2012
DOI: 10.1590/s1415-790x2012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da dieta de adolescentes: estudo de base populacional em Campinas, SP

Abstract: O objetivo deste estudo foi avaliar a qualidade global da dieta e a adequação do consumo de cada componente da dieta de adolescentes segundo fatores demográficos, socioeconômicos e índice de massa corporal (IMC). Trata-se de estudo transversal, de base populacional, que analisou amostra representativa de 409 adolescentes, de 12 a 19 anos, utilizando o Índice de Qualidade da Dieta (IQD). Foram estimadas as prevalências de dietas classificadas no 1º quartil do IQD e as médias de escores de cada componente do IQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
3
14
0
13
Order By: Relevance
“…In Most of the patients in this study were self-declared as brownish colour (47.3%), followed by white colour 12 , as shown in a study in which higher education levels were associated with a higher consumption of vegetables, fruits, milk and dairy products and a high variety of diet 13 .…”
Section: Sociodemographic Characterizationmentioning
confidence: 50%
“…In Most of the patients in this study were self-declared as brownish colour (47.3%), followed by white colour 12 , as shown in a study in which higher education levels were associated with a higher consumption of vegetables, fruits, milk and dairy products and a high variety of diet 13 .…”
Section: Sociodemographic Characterizationmentioning
confidence: 50%
“…In research that analyzed the scores for Healthy Eating Index-2005 of three groups of different age groups, there was a tendency of a worsening in the quality of eating in the age groups between 2-17 years old and a trend for improved quality of eating in the age groups of 18 to 64 and for the over 65s 12 . A study based on information from the ISACAMP survey on health did not detect differences in the quality of the diet with the increase in the age from 12 to 19 years 34 , but the other study on the elderly population, with the same database, found a better quality of food in the individuals that were 80 years old or over compared with those aged 60 to 69 years old 35 .…”
Section: Discussionmentioning
confidence: 92%
“…Study outcomes and index scores were found in 28 studies: seven of these evaluated the relationship of the index with socioeconomic and demographic factors and food items 17,[31][32][33][34][35][36] ; eight studies evaluated the relationship with socioeconomic factors and health [37][38][39][40][41][42][43][44] ; five studies evaluated the relationship with health outcomes [45][46][47][48][49] ; four studies evaluated the relationship with nutrients [50][51][52][53] ; two studies evaluated the relationship with some type of intervention 15,54 ; one study evaluated the relationship with nutrients and food items 55 ; and one study evaluated the relationship with socioeconomic and demographic factors 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers use the term Healthy Eating Index [13][14][15][18][19][20][21]23,24,[27][28][29][30][31]33,34,[36][37][38]40,42,[45][46][47]50,[52][53][54] , while other studies refer to the Dietary Quality Index 11,12,17,22,25,26,32,35,39,41,43,44,48,49,51,55,56 . Some authors referred to using the Dietary Quality Index when they published in Brazilian journals and the Healthy Eating Index when they published in international journals, reinforcing the lack of standardization in relation to nomenclatures regarding indices.…”
Section: Discussionmentioning
confidence: 99%